Investigating the impact of terrorist attacks on the mental health of emergency responders: systematic review - Wesemann, U; Applewhite, B; Himmerich, H (Cambridge University Press, 2022)
Background Terrorist attacks have strong psychological effects on rescue workers, and there is a demand for effective and targeted interventions. Aims The present systematic review aims to examine the mental health outcomes of exposed emergency service personnel over time, and to identify risk and resilience factors. Method A literature search was carried out on PubMed and PubPsych until 27 August 2021. Only studies with a real reported incident were included. The evaluation of the study quality was based on the Quality Assessment Tool for Quantitative Studies, and the synthesis used the ‘Guidance on the Conduct of Narrative Synthesis in Systematic Reviews’. Results Thirty-three articles including 159 621 individuals were identified, relating to five different incidents with a post-event time frame ranging from 2 weeks to 13 years. The post-traumatic stress disorder prevalence rates were between 1.3 and 16.5%, major depression rates were between 1.3 and 25.8%, and rates for specific anxiety disorders were between 0.7 and 14%. The highest prevalence rates were found after the World Trade Center attacks. Reported risk factors were gender, no emergency service training, peritraumatic dissociation, spatial proximity to the event and social isolation. Conclusions The inconsistency of the prevalence rates may be attributable to the different severities of the incidents. Identified risk factors could be used to optimise training for emergency personnel before and after catastrophic events. Voluntary repetitive screening of rescue workers for mental health symptoms is recommended.